Effects of ALA-PDT on the Healing of Mouse Skin Wounds Infected With Pseudomonas aeruginosa and Its Related Mechanisms - Yang, Tao; Tan, Yang; Zhang, Wentao; Yang, Weijiang; Luo, Jiefu; Chen, Ling; Liu, Hong; Yang, Guihong; Lei, Xia (Frontiers in Cell and Developmental Biology, 2020)
Photodynamic therapy (PDT) is a promising new method to eliminate microbial infection and promote wound healing. Its effectiveness has been confirmed by some studies; however, the mechanisms of PDT in wound healing remain obscure. We used mouse skin wounds infected with Pseudomonas aeruginosa as a research object to explore the therapeutic effects and mechanisms of 5-aminolevulinic acid photodynamic therapy (ALA-PDT). ALA-PDT treatment significantly reduced the load of P. aeruginosa in the wound and surrounding tissues and promoted the healing of skin wounds in mice. Hematoxylin-eosin (HE) and Sirius red staining showed that ALA-PDT promoted granulation tissue formation, angiogenesis, and collagen regeneration and remodeling. After ALA-PDT treatment, the expression of inflammatory factors (TNF-α and IL-1β) first increased and then decreased, while the secretion of growth factors (TGF-β-1 and VEGF) increased gradually after treatment. Furthermore, ALA-PDT affected the polarization state of macrophages, activating and promoting macrophages from an M1 to an M2 phenotype. In conclusion, ALA-PDT can not only kill bacteria but also promote wound healing by regulating inflammatory factors, collagen remodeling and macrophages. This study further clarifies the mechanism of PDT in the healing of infectious skin wounds and provides further experimental evidence for its clinical treatment of skin wounds infected by P. aeruginosa.